A differential pattern of gene expression in skeletal muscle of tumor‐bearing rats reveals dysregulation of excitation–contraction coupling together with additional muscle alterations. Issue 2 (6th November 2013) - Fontes‐Oliveira, Cibely Cristine; Busquets, Sílvia; Fuster, Gemma; Ametller, Elisabet; Figueras, Maite; Olivan, Mireia; Toledo, Míriam; López‐Soriano, Francisco J.; Qu, Xiaoyan; Demuth, Jeffrey; Stevens, Paula; Varbanov, Alex; et al.
ABSTRACT Introduction: Cachexia is a wasting condition that manifests in several types of cancer. The main characteristic of this condition is a profound loss of muscle mass. Methods: By using a microarray system, expression of several hundred genes was screened in skeletal muscle of rats bearing a cachexia‐inducing tumor, the AH‐130 Yoshida ascites hepatoma. This model induced a strong decrease in muscle mass in the tumor‐bearing animals, as compared with their healthy counterparts. Results: The results show important differences in gene expression in EDL skeletal muscle between tumor‐bearing animals with cachexia and control animals. Conclusions: The differences observed pertain to genes related to intracellular calcium homeostasis and genes involved in the control of mitochondrial oxidative phosphorylation and protein turnover, both at the level of protein synthesis and proteolysis. Assessment of these differences may be a useful tool for the design of novel therapeutic strategies to fight this devastating syndrome. Muscle Nerve49: 233–248, 2014